2011
DOI: 10.1002/cpp.767
|View full text |Cite
|
Sign up to set email alerts
|

Inference‐Based Therapy for Body Dysmorphic Disorder

Abstract: Body dysmorphic disorder (BDD) is a debilitating disorder characterized by an excessive preoccupation with an imagined or very slight defect in one's physical appearance. Despite the overall success of cognitive behavioural therapy (CBT) in treating BDD, some people do not seem to benefit as much from this approach. Those with high overvalued ideation (OVI), for instance, have been shown to not respond well with CBT. The purpose of this study was to evaluate the efficacy of an inference-based therapy (IBT) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 28 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…[35] BODY DYSMORPHIC DISORDER BDD has been included in the OCRDs chapter of DSM-5 due to similarities between BDD and OCD across many validators, including repetitive behaviors. [40,42] Moreover, BDD patients have been found to have an increased likelihood of being diagnosed with a psychotic disorder due to BDD or OCD-related delusional beliefs. [2] The core feature of BDD has remained unchanged, however-distressing or impairing preoccupation with perceived appearance defects or flaws that are not observable or appear slight to others.…”
Section: Why Have the Other Disorders Been Included In The New Ocd Sementioning
confidence: 99%
See 3 more Smart Citations
“…[35] BODY DYSMORPHIC DISORDER BDD has been included in the OCRDs chapter of DSM-5 due to similarities between BDD and OCD across many validators, including repetitive behaviors. [40,42] Moreover, BDD patients have been found to have an increased likelihood of being diagnosed with a psychotic disorder due to BDD or OCD-related delusional beliefs. [2] The core feature of BDD has remained unchanged, however-distressing or impairing preoccupation with perceived appearance defects or flaws that are not observable or appear slight to others.…”
Section: Why Have the Other Disorders Been Included In The New Ocd Sementioning
confidence: 99%
“…[41] Probably the most clinically significant change to the diagnostic criteria of BDD is the inclusion of the delusional form of the disorder, noted by an insight specifier, "absent/delusional beliefs." [45] When insight is low or absent and OVI is high, techniques such as motivational interviewing [37] or inference-based therapy [42] may be helpful. [40,42] Moreover, BDD patients have been found to have an increased likelihood of being diagnosed with a psychotic disorder due to BDD or OCD-related delusional beliefs.…”
Section: Why Have the Other Disorders Been Included In The New Ocd Sementioning
confidence: 99%
See 2 more Smart Citations
“…Studies have demonstrated that IBT is equally effective in individuals with OVI and individuals without OVI [30][31][32]. IBT has been adapted to treat individuals with EDs [33].…”
Section: Treatmentmentioning
confidence: 99%